2017
DOI: 10.1038/nutd.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypovitaminosis D and associated factors in obese Spanish children

Abstract: Background/Objectives:Vitamin D deficiency may contribute to endocrine health and disease (diabetes, autoimmune thyroid diseases, polycystic ovarian syndrome, etc.). The aim of this study was to determine the prevalence and specific factors for hypovitaminosis D among children stratified by body mass index (BMI) in Northern Spain.Subjects/Methods:A cross-sectional clinical (sex, age, season of study visit, place of residence and BMI) and blood testing (calcium, phosphorous, calcidiol and parathyroid hormone (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 33 publications
(62 reference statements)
4
41
2
6
Order By: Relevance
“…On the other hand, obesity is a known risk factor for Vitamin D deficiency. In fact, circulating concentration of 25(OH)D is inversely associated with the severity of obesity [6][7][8]. Data on the relationship between hypovitaminosis D and the different components of metabolic syndrome, both in adults [9][10][11] and children with obesity [12][13][14][15][16] are, at present, inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, obesity is a known risk factor for Vitamin D deficiency. In fact, circulating concentration of 25(OH)D is inversely associated with the severity of obesity [6][7][8]. Data on the relationship between hypovitaminosis D and the different components of metabolic syndrome, both in adults [9][10][11] and children with obesity [12][13][14][15][16] are, at present, inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…The mean serum calcidiol content in blood serum of adolescents with obesity was 1.43 times lower than that of children with normal body weight. The data obtained during the study showed a similar trend of change in the status of vitamin D in children of different ages during epidemiological studies in Ukraine, but were lower compared with the data of the studies in the USA, Spain, and Italy 5,9 . Researchers explain the low levels of 25 (OH) D in blood serum by depositing calcidiol in the adipose tissue, reducing bioavailability, and reducing its synthesis under the influence of ultraviolet rays 14 .…”
Section: Discussionmentioning
confidence: 42%
“…Anthropometric examinations -body weight (within the accuracy of 0.1 kg), height (within the accuracy of 0.1 cm) -were carried out, with the use of generally accepted methods with the help of floor weight, height meter and flexible centimeter tape. BMIs were evaluated according to standard percentile tables 5,14 . Thus, children with BMI from 15 to 85 percentiles were assigned to the normal body mass, the excess body mass corresponded to 85-95 percentiles and over 95 percentiles -to the obesity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations